2023
DOI: 10.1371/journal.pone.0281468
|View full text |Cite
|
Sign up to set email alerts
|

B.Y.O. Bees: Managing wild bee biodiversity in urban greenspaces

Abstract: As cities become more populated and the density of urban development increases, local biodiversity is threatened. Urban greenspaces have the capacity to preserve pollinator biodiversity, but the quality of support they provide depends on greenspace landscape attributes, including the availability of pollinator habitat and foraging resources. Wild native bees provide important pollination services to urban ecosystems, yet relatively little is known about how urban landscape management influences pollinator comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Indeed, one study found that planting "bee-friendly" plants next to strawberry plants increased the yield and fruit quality in an urban area [94]. Urban conservation strategies to boost pollinator diversity, including sewing native wildflower strips, reducing pesticide use, or limiting mowing in urban green spaces [19,28], could promote pollinator diversity and the production of high-quality urban crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, one study found that planting "bee-friendly" plants next to strawberry plants increased the yield and fruit quality in an urban area [94]. Urban conservation strategies to boost pollinator diversity, including sewing native wildflower strips, reducing pesticide use, or limiting mowing in urban green spaces [19,28], could promote pollinator diversity and the production of high-quality urban crops.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects of urban landscapes can allow cities to harbour diverse pollinator communities [25][26][27]. Despite a growing interest in urban pollinator diversity [28][29][30] and their pollination services [17,21,31,32], few studies assess whether these unique urban pollinator communities can provide sufficient pollination services to support urban crop production.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of our knowledge about pollination and pollinators focus on diurnal activity, neglecting the contribution of nocturnal pollinators to crop production [13,28]. Night-active pollinators include vertebrates such as bats (under tropical climates) as well as invertebrates such as moths, beetles and some bee species [28][29][30][31][32][33][34][35][36]. Some studies have investigated whether nocturnal pollinators contribute to crop pollination.…”
Section: Introductionmentioning
confidence: 99%